2017
DOI: 10.1111/ene.13440
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 and risk of ischaemic stroke: Reasons for Geographic and Racial Differences in Stroke cohort

Abstract: Galectin-3 was associated with incident ischaemic stroke in younger but not older individuals. Confirmation of this finding, and elucidation of its implications for stroke pathophysiology and prevention, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Some studies showed that elevated galectin‐3 was associated with incident ischaemic stroke in young individuals , as well as cerebrovascular ischaemic events in patients who underwent carotid endarterectomy . Meanwhile, a case–control study showed that galectin‐3 was significantly higher in patients with poor functional outcomes than in those with good outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that elevated galectin‐3 was associated with incident ischaemic stroke in young individuals , as well as cerebrovascular ischaemic events in patients who underwent carotid endarterectomy . Meanwhile, a case–control study showed that galectin‐3 was significantly higher in patients with poor functional outcomes than in those with good outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…A prospective longitudinal cohort study enrolled 30 239 patients in the Southeastern United States between 2003 and 2007, and determined baseline plasma galectin-3 levels for 1453 participants selected by a stratified sampling method to include high-risk groups. 130 Within this cohort of 1453 people, by 2011, a total of 526 developed an ischemic stroke. Using a case-cohort study design, serum galectin-3 levels in the upper 2 quartiles were associated with 2.3-fold increased stroke risk (95% CI = 1.6-3.4).…”
Section: Lifestylementioning
confidence: 99%
“…A recent study based on the REGARDS cohort of blacks and whites found that Galectin-3 levels were associated with ischemic stroke incidence in individuals who were younger than 64 years of age [3] . The reason for such an association with age is not clear, but it is possible that levels correlate with a generalized worsening of metabolic syndrome markers, which are more likely to pass the diagnostic threshold later in life.…”
Section: Ischemic Strokementioning
confidence: 99%
“…Although most of the attention in the research literature on the carbohydrate-binding lectin Galectin-3 has focused on cardiovascular pathology [1] , especially in heart failure [2] , there have been some recent studies discussing its role in cerebrovascular disease [3,4] . However, the results of these studies have not been completely consistent with each other [5][6][7][8] , and awareness in the neurosciences community about this biomarker remains limited.…”
Section: Introductionmentioning
confidence: 99%